2011
DOI: 10.1007/s11666-011-9628-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Si, Mg, CO3 2− Substituted Hydroxyapatite Coatings Deposited by Liquid Precursor Plasma Spraying: Synthesis and Characterization

Abstract: In this study, a novel liquid precursor plasma spraying (LPPS) process was used to deposit Si, Mg, CO 3 22 substituted hydroxyapatite (HA) coatings (alone and cosubstituted) onto Ti-6Al-4V substrates. Salts of silicon, magnesium, and carbonate elements were directly added into the HA liquid precursor for subsequent plasma spraying. The phase composition, structure, and morphology of all HA coatings were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…Numerous studies showed that both a - and c -axis dimensions increased with the silicon content [18, 29, 30]. Considering the substitution of SiO 4 4− in the CO 3 Ap, it is possible that, a - and c -axis dimensions are higher than those of CO 3 Ap (Table 3) because the ionic bond length of a Si–O bond (0.166 nm) is greater than that of P–O bond (0.157 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies showed that both a - and c -axis dimensions increased with the silicon content [18, 29, 30]. Considering the substitution of SiO 4 4− in the CO 3 Ap, it is possible that, a - and c -axis dimensions are higher than those of CO 3 Ap (Table 3) because the ionic bond length of a Si–O bond (0.166 nm) is greater than that of P–O bond (0.157 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal domain size along c-axis can be increased by some trace elements (SiO 4 4- , CO 3 2- , Zn 2+ , Fe 2+ , Fe 3+ and Sr 2+ ) and decreased by others (Mg 2+ , Ni 2+ , Cr 3+ , Co 2+ and Ti 4+ ). Some trace elements can increase the crystallinity (degree of structural order of atoms) and crystal domain size (average length of individual crystals) of synthetic HA (Cr 3+ , Co 2+ and Ni 2+ ), while others have the opposite effect (SiO 4 4- , Zn 2+ , CO 3 2- , Fe 2+ , Ti 4+ , Sr 2+ , Ce 3+ and Mg 2+ ) (Christoffersen et al 1997; Ergun 2008; Feng et al 2005; Hu et al 2007; Huang et al 2011; Li et al 2008; Lin et al 2007; Mabilleau et al 2010; Morrissey et al 2005; Ren et al 2010; Ribeiro et al 2006; Tang et al 2005; Wang et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated the obtainment of dense and uniform films with a surface of nanorods (diameters between 30 and 50 nm), characterised by enhanced HAp dissolution resistance, due to the fluorine incorporation and to the nanosized structure, and improved bonding strength. Furthermore, silicate ions were co‐substituted within HAp coatings with Mn 2+ , Sr 2+ , Mg 2+ . In details, Büyükaksoy et al fabricated Mn/Si co‐substituted hydroxyapatite thin films by dip coating method.…”
Section: Bi‐substituted Hydroxyapatite Coatingsmentioning
confidence: 99%
“…Similarly, some multi‐substituted HAp coatings were proposed and tested. Huang et al produced Si/Mg co‐doped carbonate HAp coatings by liquid precursor plasma spray and demonstrated that Si and Mg co‐presence led to reduced crystallinity and crystallite size and to the lattice distortion, evidencing the lowering of OH − band and the broadening of phosphates bands in the related FT‐IR spectra.…”
Section: Multi‐substituted Hydroxyapatite Powders and Coatingsmentioning
confidence: 99%